Peran identifikasi risiko pasar dalam meningkatkan pertumbuhan penjualan UMKM ritel di Kabupaten Sidoarjo - alghifary, lefa maulana; Prajawati, Maretha Ika (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the process of market risk identification, its role in increasing sales growth, and supporting and inhibiting factors for retail SMEs in Sidoarjo Regency. A qualitative approach with a case study method was applied to 10 retail SMEs selected purposively. The results show that market risk identification is carried out through direct observation, communication with customers, social media monitoring, and business experience. This risk identification plays a role in strategic decisionmaking, product innovation, price optimization, and building customer loyalty. Supporting factors include strong business networks and technology access, while the main obstacles are limited capital, time, and digital knowledge. This study concludes that market risk identification—although conducted informally—is key to the sales growth of retail SMEs in Sidoarjo.